How things changed during the COVID-19 pandemic's first year: A longitudinal, mixed-methods study of organisational resilience processes among healthcare workers. (November 2022) - Corbaz-Kurth, Sandrine; Juvet, Typhaine M.; Benzakour, Lamyae; Cereghetti, Sara; Fournier, Claude-Alexandre; Moullec, Gregory; Nguyen, Alice; Suard, Jean-Claude; Vieux, Laure; Wozniak, Hannah; Pralong, Jacques A.; Weissbrodt, Rafaël; et al.
Highlights: This article explores the real-world problematic situations experienced by healthcare workers during the COVID-19 pandemic's first year. Different problematic situations were not managed equally well. Teams generally anticipated and performed well with the problematic issues relating to organisational change, difficulties implementing COVID-19 guidelines and protection measures, the complexities of working from home, emotional burdens and concerns about patient care practices, the quality of care and patients in critical conditions. However, they had greater difficulties adapting to increased workloads and work schedules, conflictual relationships, and problems involving information, communication and training, and thus had more problems developing new and effective ways of working. Four organisational resilience configurations were identified, depending on teams' levels of adaptation and performance: "learning from mistakes", "effective development", "new standards" and "hindered resilience". Organisational resilience trajectories differed depending on healthcare professionals' categories, hierarchical status and the perceived severity of the problematic situations. Abstract: COVID-19 had a huge impact on healthcare systems globally. Institutions, care teams and individuals made considerable efforts to adapt their practices. The present longitudinal, mixed-methods study examined a large sample of healthcare institution employees in Switzerland. Organisational resilience processes were assessed by identifying problematic real-world situations and evaluating how they were managed during three phases of the pandemic's first year. Results highlighted differences between resilience processes across the different types of problematic situations encountered by healthcare workers. Four configurations of organisational resilience were identified depending on teams' performance and ability to adapt over time: "learning from mistakes", "effective development", "new standards" and "hindered resilience". Resilience trajectories differed depending on professional categories, hierarchical status and the problematic situation's perceived severity. Factors promoting or impairing organisational resilience are discussed. Findings highlighted the importance of individuals', teams' and institutions' meso - and micro-level adaptations and macro-level actors' structural actions.